The Jesuit missions of Paraguay and a cultural history of Utopia (1568-1789) - Imbruglia, Girolamo. (Studies in Christian Mission, 2017)
The Jesuit Missions of Paraguay and a Cultural History of Utopia (1568-1789) explores the religious foundations of the Jesuit missions in Paraguay, and the discussion of the missionary experience in the public opinion of early modern Europe, from Montaigne to Diderot. This book presents a wealth of documentation to highlight three key aspects of this debate: the relationship between civilisation and religion, between religion and political imagination, and between utopia and history. Girolamo Imbruglia's analysis of the Jesuits' own narrative reveals that the idea and the practice of mission have been one of the essential features of the European identity, and of the shaping modern political thought.